A Study of Health Problems and Nutritional Status of Tea Garden Workers of Assam - Saikia, SB; Bhattacharyya, HK; Barooah, A; Sharma, B (Journal of Agricultural Extension Management, 2018)
A study was conducted to ascertain the socioeconomic profile of tea garden workers of Assam, India. For the purpose, 299 families from three different villages were selected randomly and the socioeconomic profile was collected through a pre-scheduled structured questionnaire. The study revealed that children between 3-6 years of age and also the mothers suffered from stunted body growth. High rates of illiteracy were found in the study area and this led to marriage of the girls at a very young age. Average income of the families was very less with most of the people living in katcha house only. The study concludes that the socioeconomic condition of this section of the people of Assam may be upgraded through mass awareness programmes and emphasis on nutrition and health care